Hypoglycemic effect of white (Morus alba L.) and black (Morus nigra L.) mulberry fruits in diabetic rat - Mahmoud, Hemdan Ibrahem; ElRab, Said Mnaa Gad; Khalil, Ayman Fathey; Ismael, Samah Mohamed (European Journal of Chemistry, 2014)
The aim of the present study was to investigate the hypoglycemic effect of white (Morus alba L.) and black (Morus nigra L.) mulberry fruits either used individually or in a combination on alloxan diabetic rats. These fruits are reported to be rich in antioxidants, flavonoids and phenolics that can potentially fight against diabetes mellitus. Male albino rats were divided into 5 groups: normal control, alloxan-diabetic control, diabetic rats treated with white mulberry fruit powder at 5% in the diet, diabetic rats treated with black mulberry fruit powder at 5% in the diet and diabetic rats treated with mixture of white and black mulberry fruits powder at 5% in the diet. After 4 weeks of treatment, blood glucose level, liver and kidney enzymes activity, lipid profile, lipid peroxidation and histopathological studies on liver, kidney and pancreas were evaluated. The mixture of white and black mulberry fruits showed the most significant (p < 0.05) improvement in feed efficiency ratio with increasing body weight gain, as well as decrease in blood glucose level and liver-kidney dysfunction when compared with diabetic control rats. Significant decrease in serum cholesterol, triglycerides and low density lipoprotein cholesterol (LDLc) as well as significant increase in high density lipoprotein cholesterol (HDLc) in diabetic rats was observed with all treatments. Moreover, mulberry fruits administration caused significant inhibition in lipid peroxidation and α-amylase activity. In addition, the beneficial effect of all treatments was further confirmed with histopathological examination of liver, kidney and pancreas. This study reveals hypoglycemic and hypolipidemic effects of white and black mulberry fruits either used individually or in combination as a dietary supplement in alloxan diabetic rats.